Comprehensive physically based modelling and simulation of power diodes with parameter extraction using MATLAB. Issue 10 (1st October 2014) - Shaker, Ahmed; Abouelatta, Mohamed; Sayah, Gihan Taha; Zekry, Abdelhalim
Abstract : In this study, we present an improved comprehensive model of power diodes. This model is based on the numerical solution of the ambipolar diffusion equation (ADE) by a modified finite difference method using MATLAB. The ADE is solved for all levels of injection instead of high‐level injection only as usually done. Local physical effects such as conductivity modulation, emitter recombination, carrier–carrier scattering and lifetime control are taken into consideration. Temperature and self‐heating effects are also included in the model. The proposed model has been validated against Silvaco mixed‐mode simulations showing very good agreement with much less simulation times for our model. To be self contained, we also present a model parameter extraction methodology for power diodes given their experimental transient waveforms.